Electrochemical removal of brilliant green dye from wastewater. Issue 1 (July 2020) - Aqeel, Khalifah; Mubarak, Hayfaa A.; Amoako-Attah, Joseph; Abdul-Rahaim, Laith A.; Al Khaddar, Rafid; Abdellatif, Mawada; Al-Janabi, Abuduljaleel; Hashim, Khalid S.
Abstract: Dyes are one of the most widely used materials in many industrial fields as coloring agents such as textile, wood, and food manufacturing. As these dyes end up in a water source, this high rate of dyes use represents one of the severe risks to the environment and health organizations. Most of the dyes are considered as highly toxic compounds and dangerous to the environment and human health as it consists of heavy metals, carcinogenic elements, oxygen – absorbing chemicals, and other toxic compounds that need to be well treated before discharge them back to environment. As a result, federal legislations have directed that all industrials that waste dyes-containing effluents to ensure a full dyes removal before discharging their effluents back to water bodies. Industries have applied many different treatment methods including physical, chemical, and biological methods in order to meet the required legislations. In recent years, many industries started to use electrocoagulation as the main treatment method. This study is focusing on using electrocoagulation (EC) method to remediate artificial colored effluents from coloring agents (brilliant green dye (BG dye) as a model). Electrocoagulation reactor, uses aluminum electrodes, was employed to remove this dye under different initial pH (40-10.0), direct currents (DC) (244-732 mA), and spaces between electrodes (SBE) (4-12 mm). According to the findings obtained, EC was highly efficient in treatment of colored effluents; 95.3% of BG dye was removed at treatment time, SBE, DC and pH of 30 minutes, 4 mm, 488 mA and 7.0, respectively.